Pengembangan Aplikasi Booking Online Preschool Berbasis Website - Rahayu, Sri; Fitriyani, Leni; Mubarok, Yusuf (Jurnal Algoritma, 2024)
Pre-school means a program for children aged 3 to 5 years, before entering kindergarten. Until now it has become commonplace for children aged 2 to 3 years to enter pre-school. The pre-school booking process uses social media such as Whatsapp, Instagram and Facebook, but the drawback is that it is hampered by detailed information such as status, the booking data collection process is less structured so it is difficult to carry out bookkeeping. The aim of this research is to produce a website-based online pre school booking application in Kober Al Utama, Sukanagara District, Cianjur Regency which can assist pre schools in collecting data on facilities and schedules as well as the booking process carried out by parents. The methodology used for this research is RUP (Unified Modeling Language) with the stages of Inception, Elaboration, Construction. And the modeling uses UML (Unified Modeling Language) and uses Alpha testing using the Black Box Testing method. The research results are in the form of a website-based online pre school booking application. This application can help the public in carrying out the booking process.